A Mechanistic Accumulator Model for RETRAN-3D. (3rd April 2018) - Kadakia, Hiral; Baker, Andrew; Paulsen, Mark
Abstract: RETRAN-3D is a versatile and reliable best-estimate five-equation thermal-hydraulic analysis code used for anticipated operational occurrences and for small-break loss-of-coolant accidents transient analysis of light water reactor systems. The RETRAN-3D accumulator model has been revised to predict behavior during short-intermediate and long-term transients in pressurized water reactors. The accumulator is a single-volume, two-region nonequilibrium component model that includes vessel geometry, wall metal mass, and wall and liquid region surface areas as a function of level. The model accounts for heat transfer effects from the vessel wall to the vapor region using a lumped parameter model and accounts for heat transfer from the liquid region to the gas region. Mass and energy balance equations are solved for the liquid region, and an energy equation is solved for the vapor region. A pressure equation of state provides the pressure as a function of the mass and energy of the liquid and vapor regions. The new model is validated with loss-of-fluid test and semiscale experimental data, demonstrating that the model is capable of predicting the behavior of an accumulator for transients ranging from short term to long term and accounts for the effects of accumulator geometry such as surface area-to-volume ratio.